1996
DOI: 10.1111/j.1432-1033.1996.0150u.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterisation of an α‐Glucan Phosphorylase from the Thermophilic Bacterium Thermus thermophilus

Abstract: An a-glucan phosphorylase has been purified 4500-fold from the thermophilic bacteria Thermus thermophilus. In contrast to other bacterial phosphorylases the thermophilic enzyme seems neither to be inducible by maltose nor repressed by glucose. 7: tliernzophilus phosphorylase shares major properties with known mesophilic phosphorylases such as pyridoxal 5'-phosphate content (1 M pyridoxal-PIM subunit), subunit molecular mass (about 90 kDa) and inhibitor constants. The optimum temperature of 7: therniophilus pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The minimum primer for glucan synthesis reaction and the minimum effective substrate for phosphorylation of the enzyme from T. aquaticus are maltotriose and maltotetraose, respectively. These values corresponded well to those of the enzyme from Thermus thermophilus, 29) but are one unit shorter than those of potato enzyme.…”
supporting
confidence: 66%
“…The minimum primer for glucan synthesis reaction and the minimum effective substrate for phosphorylation of the enzyme from T. aquaticus are maltotriose and maltotetraose, respectively. These values corresponded well to those of the enzyme from Thermus thermophilus, 29) but are one unit shorter than those of potato enzyme.…”
supporting
confidence: 66%
“…Many of the mal genes from E. coli, including the global regulator malT and those encoding MalQ, MalP, and MalZ, have homologues in the genome of strain HB27 (4,12). In strain HB8, the 4-␣-glucanotransferase (MalQ) (TTC0897 in HB27) had very low activity with maltose, the maltodextrin glucosidase (MalZ) (TTC1283 in HB27) has been found to hydrolyze sucrose and maltose, and the maltodextrin phosphorylase (MalP) (TTC0808 in HB27) hydrolyzed maltooligosaccharides and glycogen but not maltose (3,17,30). In Bacillus species, maltose can be taken up and hydrolyzed to glucose and glucose-1-phosphate by a maltose phosphorylase, which is absent from strain HB27 (14).…”
Section: Discussionmentioning
confidence: 99%
“…The smallest maltooligosaccharides typically accepted for the phosphorolysis and glucosylation by α-glucan phosphorylase isolated from plants such as potato are maltopentaose (Glc 5 ) and maltotetraose (Glc 4 ), respectively. On the other hand, it was reported that the smallest substrates accepted by α-glucan phosphorylase isolated from thermophilic bacterial sources (thermostable α-glucan phosphorylase) for the former and latter reactions were Glc 4 and maltotriose (Glc 3 ), respectively (20)(21)(22). These observations indicate that α-glucan phosphorylases exhibit different recognition behaviors for the substrates depending on their sources.…”
mentioning
confidence: 73%